Association between delivery mode and pelvic organ prolapse: A meta-analysis of observational studies. (April 2019) - Leng, Bingjie; Zhou, Yong; Du, Shuguo; Liu, Fang; Zhao, Lei; Sun, Guoqiang; Zhao, Yun
Abstract: Pelvic organ prolapse (POP) is a common disease in aged women with negative physical and psychological influences. The long-term impact of delivery mode on POP remains uncertain. To evaluate the relationship between delivery mode and POP, a meta-analysis was carried out in this study. PubMed, Web of Science and CENTRAL were combined to search for relevant studies. Data were extracted by two investigators independently. Odd ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by a random-effects model. Sensitivity analysis was performed to explore the potential source of heterogeneity. Moreover, Begg's and Egger's tests were conducted to assess the publication bias of included studies. In total, 13 eligible studies were included in our meta-analysis. Among them, six studies using objective standards for POP definition were included in Group 1, 5 studies addressing the women's own perception of POP were included Group 2, and the remaining 2 studies with both objective and subjective measures for POP assessment were included in both group 1 and group 2. Pooled estimates in our study demonstrated increased risk of POP after any vaginal delivery vs. cesarean section (Group 1 : OR = 7.69; 95% CI = 4.89, 12.07; heterogeneity: P = 0.00, I 2 = 85.8%.Group 2 : OR = 2.22; 95% CI = 1.72, 2.87; heterogeneity: P = 0.10, I 2 = 43.5%). Similar results were found in the comparison of spontaneous vaginal births only vs. cesarean sections (Group 1 : OR = 7.76; 95% CI = 4.43, 13.60;Group 2 : OR = 2.08; 95% CI = 1.50, 2.89). There was no significant difference in POP between assisted vaginal delivery (including vacuum and forceps) and spontaneous vaginal births. Compared with cesarean sections, vaginal delivery (including women delivering only by spontaneous vaginal births and women with both vaginal and cesarean deliveries) is associated with an increased risk of long-term POP.